2010
DOI: 10.1136/jnnp.2009.198192
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic lesions in multiple sclerosis

Abstract: Hypothalamic lesions in MS are more frequent than previously reported and are not associated with NMO-IgG antibody.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 23 publications
2
18
2
3
Order By: Relevance
“…For example, if characteristic periependymal or hypothalamic disease is apparent, our data would suggest a diagnosis of NMO/AQP4 antibody associated disease to be highly likely. However, other authors have found hypothalamic lesions in 13.3% of 105 Caucasian patients with classical MS [26]. As this data indicates that hypothalamic lesions can be seen in classical MS, and our series is biased, we do not conclude that the presence of hypothalamic disease alone excludes the diagnosis of MS.…”
Section: Discussioncontrasting
confidence: 60%
“…For example, if characteristic periependymal or hypothalamic disease is apparent, our data would suggest a diagnosis of NMO/AQP4 antibody associated disease to be highly likely. However, other authors have found hypothalamic lesions in 13.3% of 105 Caucasian patients with classical MS [26]. As this data indicates that hypothalamic lesions can be seen in classical MS, and our series is biased, we do not conclude that the presence of hypothalamic disease alone excludes the diagnosis of MS.…”
Section: Discussioncontrasting
confidence: 60%
“…For example, the corpus callosum was suggested to be a differentiating point between NMO and MS [2]. In our previous study using conventional MRI protocols, hypothalamic lesions could be detected in 13.3% of MS patients but were not found in any patients with NMO [3]. Thus, our results do not support the suggestion that hypothalamic lesions were specific to NMO.…”
Section: Introductioncontrasting
confidence: 75%
“…Pittock and colleagues reported that 60% of NMO patients show brain abnormalities on MRI, with about 10% developing NMO-unique hypothalamic, corpus callosal, periventricular, or brainstem lesions (74) in regions enriched for the target antigen, AQP4 (76, 81, 108). However, in contrast to MS, NMO brain lesions may be reversible.…”
Section: Anatomical Distribution Of Nmo Lesions In the Cnsmentioning
confidence: 99%